Enhancement of Dental Health, Utilization of Dentures, and Nutritional Status in Adolescents with Beta Thalassemia Major in DKI Jakarta - Pradypta, Putu Gyzca; Prawesthi, Endang; Marsigid, Didik; Tarsilah, Tarsilah; Maesaroh, Imas; Nareswara, Anastu Regita (Warta LPM, 2025)
Background of the problem: Adolescents with thalassemia often experience dental health problems due to disease complications and treatment. Prevention can be achieved by improving nutritional status and public education about thalassemia. The program activities that can be a solution to these problems are through education. Objectives: This service aims to improve dental health, understanding of the use of dentures, and nutritional status among adolescents with Beta Thalassemia Major in DKI Jakarta. Methods: The methods used in this activity include socialization and counseling on dental health and thalassemia disease, which were attended by 40 adolescents from the Indonesian Thalassemia Foundation in DKI Jakarta. The stages of the activity include the distribution of activity information, the completion of a pre-test questionnaire, presentation of the material, examination, and evaluation session. Results: The post-test results of the community service activity revealed that 57.5% of participants fell into the high knowledge category, 37.5% into the moderate category, and 5.0% into the low category. Conclusion: This indicates that after this activity, there was an increase in understanding regarding efforts to improve nutritional health, the use of dentures, and the nutritional status of adolescents with beta thalassemia. Recommendations or follow-up: The intervention in the form of socialization and counseling has successfully increased the knowledge of nutritional health, dentures, and the nutritional status of adolescents with beta-thalassemia.